Madrasahs as Stewards of Living Heritage: Approaches for Cultural Continuity in Islamic Education - Akbar Yusgiantara, S.Pd. (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Madrasahs in Muslim-majority cultures serve as centers of religious education and as guardians of living heritage, safeguarding communal memory, cultural values, and intangible traditions. However, globalization, secularization, and uniform educational changes progressively jeopardize their heritage-focused functions. This study utilizes a narrative literature review (2015–2025) to examine how madrasahs navigate the equilibrium between tradition and innovation in preserving cultural continuity. Three principal domains arise: curriculum contextualization, which incorporates local cultural practices into Islamic education; community engagement, which fortifies the intergenerational transfer of knowledge and values; and digital adaptation, which facilitates the preservation and dissemination of intangible heritage via contemporary platforms. The results demonstrate that although madrasahs successfully preserve cultural identity, inconsistent policy backing, unequal execution, and inadequate digital infrastructure impede systematic integration. The study reconceptualizes madrasahs as dynamic entities that bolster legitimacy and relevance via the integration of religious education and historical preservation. It underscores the imperative for cooperative initiatives among politicians, educators, and cultural institutions to institutionalize heritage-based education and avert cultural stagnation. This research situates madrasahs within the language of cultural sustainability, contributing to broader discussions on Islamic pedagogy, educational adaptation, and the role of faith-based institutions in preserving living legacy in the twenty-first century.